FERTILITY AND PLASMA PROGESTERONE PROFILE IN REPEAT BREEDING COWS AND BUFFALOES IN OVSYNCH AND MID-CYCLE PGF2alha TREATMENT PROTOCOLS - PARMAR, CHIRAG P; PATEL, D M; HADIYA, K K; DHAMI, A J; BUHECHA, K V; SARVAIYA, N P (The Indian Journal of Animal Reproduction, 2023)
Twenty repeat breeding cows and buffaloes each were equally divided into two treatment groups, viz., Ovsynch and mid-cycle PGF2a protocols. Ten each normal cyclic cows and buffaloes exhibiting estrus within 90 days postpartum and bred served as control. All the repeat breeding cows and buffaloes under both the protocols exhibited induced estrus within 72 to 96hrs from the time of PGF 2a injection. The first service conception rates at induced estrus obtained in repeat breeding cows and buffaloes under Ovsynch protocol were 50.00 and 40.00 %, and under mid-cycle PGF2a treatment 40.00 and 50.00 %, respectively. The overall pregnancy rates of three cycles post-treatment with Ovsynch and mid-cycle PGF2a protocol were 70.00 and 60.00 % in cows and 60.00 and 70.00 % in buffaloes, respectively. In normal cyclic control cows and buffaloes also the conception rates at first Al were 40.00 and 40.00 % and those of overall of three cycles 70.00 and 60.00 %, respectively. The mean plasma progesterone concentrations in cows on day 0, 7, 9(AI) of Ovsynch treatment protocol and on day 21 post-Al were 10.60±1.57, 9.51±2.34, 0.97±0.22 and 6.62±1.69 ng/ml, respectively. The corresponding values for buffaloes were 4.59±1.17, 5.69±1.14, 0.64±0.12 and 3.59±1.26 ng/ ml. Similarly, the mean plasma progesterone concentrations in cows under mid-cycle PGF2a protocol on day of PGF2a injection, day of induced estrus/Al and day 21 post-Al were 5.61±1.66, 0.92±0.16 and 4.08±1.58 ng/ml, and in buffaloes 5.22±1.14, 0.37±0.62 and 4.29±1.27 ng/ml, respectively. The mean plasma P4 concentrations of normal cyclic cows and buffaloes on day of Al were 0.70±0.09 and 0.59±0.07 ng/ml and on day 21 postAl 4.23±1.56 and 3.69±1.20 ng/ml, respectively. Conceived animals in each group had significantly higher plasma progesterone on day 21 post-Al as compared to values in non-conceived animals. In conclusion, both the Ovsynch and mid-cycle PGF2a protocols can be effectively used to enhance pregnancy rate in repeat breeding cows and buffaloes.